Five Tuesdays in winter : stories - King, Lily (Grove Press, 2021)
"Told in the intimate voices of complex, endearing characters, Five Tuesdays in Winter intriguingly subverts expectations as it explores desire, loss, jolting violence, and the inexorable tug toward love at all costs."--Dust jacket flap.